2016
DOI: 10.1111/ajfs.12137
|View full text |Cite
|
Sign up to set email alerts
|

Market Return, Liquidity, and Trading Activity of Various Trader Types in the Emerging Market: A Study of the TAIFEX

Abstract: Using a large data set with detailed classifications of different trader types, this study sheds further light on the trading activity of various trader types on the Taiwan futures exchange (TAIFEX). Compared with domestic traders on the TAIFEX, we find that foreign institutional traders act as contrarians. In addition, when the market becomes illiquid, foreign institutional traders are net buyers and individual traders are net sellers. The result implies that both foreign institutional traders and individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(99 reference statements)
2
0
0
Order By: Relevance
“…When a trade can be classified with a trading direction, the statistics in Table 1 show that the buyer‐initiated trading volume was much greater than the seller‐initiated one, suggesting a stronger tendency to place long positions than short positions among traders on the TAIFEX. The finding is similar to that of Hao et al (2016), who showed a positive aggregated order imbalance (buyer‐initiated trades minus seller‐initiated trades) of the TXF on the TAIFEX in the sample period from 2003 to 2008. Since the data analyzed by Hao et al (2016) could identify different investor types, their results also showed that the TXF order imbalance of retail investors is positive.…”
Section: Samples Variables and Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…When a trade can be classified with a trading direction, the statistics in Table 1 show that the buyer‐initiated trading volume was much greater than the seller‐initiated one, suggesting a stronger tendency to place long positions than short positions among traders on the TAIFEX. The finding is similar to that of Hao et al (2016), who showed a positive aggregated order imbalance (buyer‐initiated trades minus seller‐initiated trades) of the TXF on the TAIFEX in the sample period from 2003 to 2008. Since the data analyzed by Hao et al (2016) could identify different investor types, their results also showed that the TXF order imbalance of retail investors is positive.…”
Section: Samples Variables and Methodssupporting
confidence: 90%
“…The finding is similar to that of Hao et al (2016), who showed a positive aggregated order imbalance (buyer‐initiated trades minus seller‐initiated trades) of the TXF on the TAIFEX in the sample period from 2003 to 2008. Since the data analyzed by Hao et al (2016) could identify different investor types, their results also showed that the TXF order imbalance of retail investors is positive. As mentioned earlier, since the raw data used in this study consists of the intraday transaction prices of the TXF only, we followed the method of Blasco et al (2012) to define the trading direction using the tick test approach.…”
Section: Samples Variables and Methodssupporting
confidence: 90%